Antimalarial drug prescriptions and clinical outcomes of febrile children in Arba Minch City, South Ethiopia - Abate Atimut Dereje; Tadesse Menjetta; Dereje Geleta; Abinet Takele; Susana Vaz Nery; Techalew Shimelis (Malaria Journal)
Abstract Background Malaria is a serious global health issue with high morbidity and mortality rates, especially among children in sub-Saharan Africa. Guidelines recommend prescribing antimalarial drugs for parasitologically-confirmed malaria. However, limited studies in Ethiopia show variable adherence to antimalarial prescribing guidelines, and the policy’s effectiveness in improving clinical outcomes remains unclear. This study aimed to assess the practice of prescribing antimalarial agents and the outcomes of fever management. Methods This prospective longitudinal study included 350 consecutive febrile children under 5 years old who presented to urban and rural health centres and a general hospital in Arba Minch City, South Ethiopia from September through December 2023. Following initial management, patient records were reviewed to collect information about demographic characteristics, clinical and blood smear microscopy findings, prescribed drugs, and hospitalization or referral status. On day 7 of follow-up, clinical outcome data were collected using a study-specific questionnaire. Blood smears were collected and examined for malaria by microscopy on day 7. Results Of 350 participants, 155 (44.3%) were from the hospital, and 195 (55.7%) were from health centres. Malaria was diagnosed by microscopy in 11.8% and 10.3% of children presenting to health centres and hospitals, respectively. In the health centres, antimalarial drugs were prescribed exclusively to patients with confirmed malaria. All children with Plasmodium falciparum infection were treated with artemether/lumefantrine (Coartem®), except two who received artesunate, while chloroquine was prescribed for all Plasmodium vivax cases. In the hospital, all patients with confirmed malaria received antimalarials, and 1.4% of those with negative microscopy results were also prescribed these drugs. By day 7, fever persisted in 9.4% of children at the hospital and 7.0% of children at health centres. During follow-up, 6.7% of children from the hospital and 1.6% from health centres sought additional care at other facilities. No deaths were reported during follow-up. Conclusion There was a high adherence to guidelines for prescribing antimalarial drugs at both higher- and lower-level healthcare facilities, accompanied by favourable clinical outcomes. However, the proportion of persistent fever and patient visits to other healthcare facilities after initial management underscores the need for additional diagnostic tools, including biomarker assays, to identify bacterial causes of fever.